GENÇLİK VE SPOR İL MÜDÜRLÜĞÜNE AİT SPOR TESİSLERİNİN YETERLİLİK DÜZEYİNİN ARAŞTIRILMASI (GÜNEYDOĞU ANADOLU BÖLGESİ ÖRNEĞİ) - ÖNER, İSMAİL (Fırat Üniveristesi, 2019)
Araştırmanın konusu " Güneydoğu Anadolu Bölgesindeki Gençlik ve Spor İl Müdürlüğüne Ait Spor Tesislerinin Yeterlilik Düzeyinin Araştırılması" dır. Araştırmanın amacı; Güneydoğu Anadolu Bölgesindeki Gençlik ve Spor İl Müdürlüğüne ait spor tesislerinin nicelik ve nitelik açısından mevcut durumu tespit edilerek, sportif faaliyetlerin uygulandığı birimlerde yer alan spor tesislerinin kullanım alanları ile yeterlilik ve kapasite düzeylerinin araştırılmasıdır. Araştırmanın evrenini; Türkiye' deki Gençlik ve Spor İl Müdürlüklerine ait spor tesisleri olup örneklemini ise; Güneydoğu Anadolu Bölgesi'ndeki Gençlik ve Spor İl Müdürlüğüne ait spor tesisleri olarak belirlenmiştir. Güneydoğu Anadolu Bölgesindeki spor tesislerinin nitelik ve nicelik açısından yeterlilik düzeyinin belirlenmek istendiği bu araştırmada 2 bölümden oluşan veri toplama aracı kullanılmıştır. Birinci bölümde Spor Tesislerinin nitelik ve nicelik olarak mevcut durumları ile ilgili bilgi toplamak amacıyla oluşturulan "Veri Toplama Formu"nun yanı sıra ikinci bölümde 2011 yılında Nacar E. tarafından Spor Tesislerinin Yeterlilik Düzeylerinin Belirlenmesine yönelik geliştirilen 25 sorudan oluşan anketin 5'li likert ölçeği kullanılmıştır. Sonuç olarak; Güneydoğu Anadolu Bölgesindeki Gençlik ve Spor İl Müdürlüklerine ait spor tesislerinin nitelik ve nicelik açısından yetersiz olduğu gözlemlenmiştir. Ayrıca müdür ve müdür yardımcıları "spor tesislerinin yetersizliğinin, siyasi iktidarların spor tesislerine gereken önemi vermediğinden" kaynaklanmadığını düşünürken, antrenör ve sporcular ise; siyasi iktidarların gereken önemi vermediğinden kaynaklandığını görüşlerine yer vermiştir.

The subject of the research is investigated the adequacy level of sports facilities which belonging to the Provincial Directorate of Youth and sports in the Southeastern Anatolia region. The aim of the research, by determining the current situation in terms of quantity and quality of sports facilities which belonging to the Provincial Directorate of Youth and sports in southeastern Anatolia region, is researched their adequacy and capacity levels with the usage areas of sports facilities in the regions where sportive activities are applied. The population of the research is the sports facilities which belonging to the Provincial Directorate of Youth and sports in Turkey. As for the sample of the research was determined as sports facilities which belonging to the Provincial Directorate of Youth and sports in the Southeastern Anatolia region. İn this research that aims to determine the qualification level of sports facilities in Southeastern Anatolia region in terms of quality and quantity, data collection tool consisting of two parts was used. In the first part, besides the 'data collection form' which is created so as to collect information about the current situation in terms of quality and quantity of sports facilities in the second part, the five-point Likert scale was used in the questionnaire consisting of 25 questions, which was developed to determine the level of competence of sports facilities by Nacar E. İn 2011. The data obtained were transferred to the computer. As a result, it was observed that the sports facilities which belonging to the ProvinciaDirectorate of Youth and sports in the Southeastern Anatolia region are insufficient in terms of quality and quantity. İn addition, while the director and deputy managers think that the lack of sports facilities is not due to the fact that the political power does not give the necessary importance to the sports facilities, as for the coach and the athletes stated that the political authorities did not give the necessary importance.
Investigation of qualification level of sport facilities of youth and sport provincial directorate (Example of southeastern anatolia region)
Keywords: Spor